Interruption of persistent exposure to leprosy combined or not with recent BCG vaccination enhances the response to Mycobacterium leprae specific antigens. - Fernanda Marques de Carvalho; Luciana Silva Rodrigues; Nádia Cristina Duppre; Iris Maria Peixoto Alvim; Marcelo Ribeiro-Alves; Roberta Olmo Pinheiro; Euzenir Nunes Sarno; Maria Cristina Vidal Pessolani; Geraldo Moura Batista Pereira (Public Library of Science (PLoS), 2017)
Household contacts of multibacillary leprosy patients (HCMB) constitute the group of individuals at the highest risk of developing leprosy. Early diagnosis and treatment of their index cases combined with Bacille Calmette-Guerin (BCG) immunization remain important strategies adopted in Brazil to prevent HCMB from evolving into active disease. In the present study, we assessed the impact of these measures on the immune response to Mycobacterium leprae in HCMB. Peripheral blood mononuclear cells (PBMC) from HCMB (n = 16) were obtained at the beginning of leprosy index case treatment (T0). At this time point, contacts were vaccinated (n = 13) or not (n = 3) in accordance with their infancy history of BCG vaccination and PBMCs were recollected at least 6 months later (T1). As expected, a significant increase in memory CD4 and CD8 T cell frequencies responsive to M. leprae whole-cell sonicate was observed in most contacts. Of note, higher frequencies of CD4+ T cells that recognize M. leprae specific epitopes were also detected. Moreover, increased production of the inflammatory mediators IL1-β, IL-6, IL-17, TNF, IFN-γ, MIP1-β, and MCP-1 was found at T1. Interestingly, the increment in these parameters was observed even in those contacts that were not BCG vaccinated at T0. This result reinforces the hypothesis that the continuous exposure of HCMB to live M. leprae down regulates the specific cellular immune response against the pathogen. Moreover, our data suggest that BCG vaccination of HCMB induces activation of T cell clones, likely through "trained immunity", that recognize M. leprae specific antigens not shared with BCG as an additional protective mechanism besides the expected boost in cell-mediated immunity by BCG homologues of M. leprae antigens.